Clinical audit for the tibial tuberosity advancement procedure - Proot, J. L. J.; Corr, S. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective To quantitatively assess the learning curve for the tibial tuberosity advancement (TTA) procedure performed by a single surgeon using the cumulative summation (CUSUM) technique and to determine if surgeon performance remained under control (i.e. within specified quality boundaries) after the learning curve had been climbed. Study design: Retrospective study.Animals Dogs (n = 122) with cranial cruciate ligament deficient stifles (n = 167).Methods Records of all dogs that had a TTA procedure performed by the same surgeon were reviewed. Cases were included if the following information was available: weight, breed, date of surgery, presence of partial or full cruciate rupture, meniscal pathology, occurrence and description of postoperative complications and treatment with a minimum of 12 months follow-up. Patients were excluded if they had a concurrent illness. Major complications were defined as those requiring revision surgery. The CUSUM technique was used to determine the time taken for the surgeon to reach a pre-defined level of competency and to monitor ongoing performance.Results Major complications occurred in 15 out of 167 procedures (9%) within 12 months of TTA surgery. The complication rate decreased as surgical experience was gained with the technique, however the learning curve continued until the 22nd procedure. Thereafter, despite the target complication rate being re-set at a lower level, the surgeon's performance remained acceptable, i.e. within the revised quality boundary.Clinical significance The CUSUM technique was used for clinical audit, to determine the learning curve for the TTA procedure for a single surgeon, and to monitor ongoing performance. An experienced general practitioner had a learning curve of 22 procedures and complication rates were within the published ranges.
Keywords: Clinical audit; tibial tuberosity advancement; cruciate; cumulative summationx